Synergy and Technology Gaps in Export Logistics Chains Between a Chilean and a Spanish Medium-Sized Port - Cordova-Gonzalez, F; Duran-San Martin, C (Elsevier B.V., 2015)
In this study we analyze the integral logistics links in a Chilean and Spanish medium-sized port to determine the synergy and technological gaps in the export logistics chain, according to the links they hold with both the business core and processes at operational level. To assess the degree of synergy in a technological context, flow-charts of each service process in the Chilean port system are provided. A comparative analysis was accomplished for a Chilean and a Spanish medium- sized port, and then we determine the key factors related to Process and Communication Technologies PCT, technological integration and collaboration among the actors in the integral logistics; at strategic and business levels, some apparent causes that may account for the technology gaps in these two ports are also analyzed at operational level. New trends to implement a port platform for the export logistics chain based on a collaborative model to improve efficiency, effectiveness and efficacy in the port are proposed. Different technologies present in export logistics chains are used to improve the management of the cargo transportation by trucks and ensure traceability and tracking of cargo from the exporter to the port. Finally, discusses the main trends in technological development in ports at the country level. © 2015 Published by Elsevier B.V.